Drought Deteriorates the N Stoichiometry of Biomass Production in European Beech Saplings Under Global Change - Köhler, Julia; Yang, Nan; Pena, Rodica; Polle, Andrea; Meier, Ina C. (Frontiers in Forests and Global Change, 2021)
Continuous nitrogen (N) deposition has raised concerns that temperate forest ecosystems shift from N limitation to progressing P limitation under global change. According to the multiple resource limitation theory, this will not only influence P economy, but also reduce N uptake and use efficiencies of trees such that growth is equally limited by N and P. We used different global change scenarios to test the prediction of this hypothesis for the N economy of European beech (Fagus sylvatica L.) saplings. Our study demonstrates that the N uptake efficiency (NUptakeE) of beech adjusts to soil N availability and stabilizes leaf and fine root N concentrations. By contrast, both efficiencies of N use were curtailed by increasing phosphorus (P) limitation under elevated soil N. The photosynthetic N use efficiency (PNUE) was serially reduced with decreasing soil P availability and increasing foliar N:P ratios, while the N use efficiency (NUE) decreased with increasing fine root N:P ratios. Soil drought induced relative P deficiency alike and reduced NUptakeE, PNUE, and NUE independent from the soil N:P ratios. We conclude that not only N deposition but also increasing summer droughts might affect N:P ratios, thereby inducing P imbalances and affecting the N economy of European beech saplings under global change.